Second-line therapies of patients initially treated with fludarabine and cyclophosphamide or fludarabine, cyclophosphamide and rituximab for chronic lymphocytic leukemia within the CLL8 protocol of the German CLL Study Group - Cramer, Paula; Fink, Anna-Maria; Busch, Raymonde; Eichhorst, Barbara; Wendtner, Clemens-Martin; Pflug, Natali; Langerbeins, Petra; Bahlo, Jasmin; Goede, Valentin; Schubert, Friederike; Döhner, Hartmut; Stilgenbauer, Stephan; et al. (Leukemia and lymphoma, 2013)
Updated results of the CLL8 trial confirm that the addition of rituximab to chemotherapy with fludarabine and cyclophosphamide (FC) leads to a prolongation of progression-free (PFS) and overall survival (OS) in first-line treatment of physically fit patients. After a median observation time of 47 months, median PFS was 57.9 months for patients treated with FC and rituximab (FCR) and 32.9 months for patients treated with FC alone (hazard ratio 0.56, 95% confidence interval 0.465-0.673; p < 0.001). A total of 232 patients were treated for relapse, among them 91 of 408 (22%) initially treated with FCR and 141 of 409 (35%) initially treated with FC. The drugs most frequently used either alone or in combination were rituximab (52% of all second-line therapies), fludarabine (21%), bendamustine (21%) and alemtuzumab (12%). The regimens chosen for second-line treatment after FC or FCR were heterogeneous, which underlines a need for further trials in order to define treatment recommendations for patients with relapsed chronic lymphocytic leukemia.
Gesehen am 27.05.2021